1991
DOI: 10.2307/2001824
|View full text |Cite
|
Sign up to set email alerts
|

Stable Rank and Approximation Theorems in H ∞

Abstract: It is conjectured that for H°° the Bass stable rank (bsr) is 1 and the topological stable rank (tsr) is 2. bsr(H°°) = 1 if and only if for every (/i > fi) G H°° x H°° which is a corona pair (i.e., there exist g, , g2 e H°°s uch that f]g1 + f2g2 = 1) there exists age H°° such that /j + f2g e (Z/00)-, the invertibles in H°° ; however, it suffices to consider corona pairs (f\ < f-¡) where /, is a Blaschke product. It is also shown that there exists age H°° such that fx + f2g 6 exp(//°°) if and only if log/j can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Let (f\, f2) £ U2(H°°(D)), which we require to show is reducible. The hypothesis of the corollary and the proof of Theorem 1.1 in [8] show that the set {Bh: B is an interpolating Blaschke product, h £ (H°°(D))~1} is dense in H°°(D). Consequently, by Corollary 1.2 in [8] there exists interpolating Blaschke products B\, B2 and h{, h2 £ (H°°(D))~l such that (1) fiBihi + f2B2h2 = I.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Let (f\, f2) £ U2(H°°(D)), which we require to show is reducible. The hypothesis of the corollary and the proof of Theorem 1.1 in [8] show that the set {Bh: B is an interpolating Blaschke product, h £ (H°°(D))~1} is dense in H°°(D). Consequently, by Corollary 1.2 in [8] there exists interpolating Blaschke products B\, B2 and h{, h2 £ (H°°(D))~l such that (1) fiBihi + f2B2h2 = I.…”
Section: Introductionmentioning
confidence: 88%
“…We note that this is then a special case of Theorem 1. More generally, Laroco [8] has shown that sr(H°°) = 1 if log/i can be boundedly analytically defined on {z : |/2(z)| < e} for some e > 0. It is also shown in [8] (Theorem 3.6) that in proving the reducibility of a general corona pair (f , f2) we can assume f is a Blaschke product.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations